Design And Building Learning Management System Application Using Scorm Model Web Based At Sma Kartika Iv-3 Surabaya - Mustafa, Putra Yoga Dwiangga; Jusak, Jusak; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The rapid development of internet technology provides ease in accessing various information from news to entertainment for free. Besides, in the world of education one of SMA Kartika IV-3 Surabaya needs to apply the internet media as a way to provide accessibility in distance learning where users can access material from anywhere which is not limited by place and time. SMA Kartika IV-3 Surabaya currently needs an online learning system to help the learning process conventionally. Another problem that arises is not yet available means to manage and facilitate the dissemination of materials to students. To solve the above problem, it can be solved with a web based Learning Management System application using SCORM model in SMA Kartika IV-3 Surabaya. At this time almost all Learning Management System using SCORM as a standard in building web based e-learning. Based on the results of testing on learning applications, shows the system used is running well. It can also engage students with teachers, generating evaluation exercises, storing materials as documents, and objects that include images, documents, video and audio premises using SCORM models accessible to teachers and administrators in one storage location.